GEMAR CETING (Healthy and Nutritious Food Movement Prevents Wasting) in School-Age Children at Public Elementary School 104209 Saentis: GEMAR CETING (Gerakan Makanan Sehat dan Bergizi Mencegah Wasting) Pada Anak Usia Sekolah di SD Negeri 104209 Saentis - Manurung, Sarida; Gultom, Risatantry; Magdalena T Bolon, Christina; Melati, Puput; BR. Sebayang, Wellina (Universitas Haji Sumatera Utara, 2025)
Nutritional problems are a global health problem that occurs almost all over the world. The impact of malnutrition will inhibit the growth process in children such as stunting and wasting, which results in a level of intelligence that is not optimal and is more susceptible to disease due to an imperfect immune system. The GEMAR CETING activity (healthy and nutritious food movement to prevent wasting) for school children is a form of health promotion activity with an educational method through counseling. From the results of observations, the problem of wasting also occurred at SD Negeri 104209 Saentis, where more than 40 out of 352 children were found to have a thin body posture, weight far below the standard growth curve or weight based on height. The purpose of this service is to increase knowledge for teachers and students about healthy and nutritious food in daily meals and the dangers of consuming unhealthy foods. The results of this service found 4 problems, namely low knowledge about wasting, not eating breakfast, unhealthy snacks and low knowledge related to child growth and development. In this service, GEMAR CETING was held by providing education to children through interesting educational videos about wasting, the importance of breakfast, healthy food and assessing child growth and development. Health promotion media is also provided to parents and teachers through leaflets and posters in the school environment. Based on the education that has been provided through educational videos, it shows that the percentage of questionnaire results on knowledge of 4 educational topics from 52.5% increased to 84.6%. The conclusion in this service is the importance of teacher involvement in detecting child growth and development and also monitoring children's snacks. Institutional support is very important in improving health promotion about healthy food and wasting.